The Effect of KMnO4 and K3[Fe(CN)6] Concentrations on Electrical Production in Fuel Cell Microbial System with Lactobacillus bulgaricus Bacteria in a Tofu Whey Substart - Ilmi Muftiana; Linda Suyati; Didik Setiyo Widodo (Jurnal Kimia Sains dan Aplikasi, 2018)
Microbial Fuel Cell (MFC) is a bioelectrochemical system that utilize metabolism of microorganisms to produce electrical energy. Microbial fuel cell is a bioelectrochemical system involving redox reactions that required an oxidizing agent in the process The purpose of this study was to determine the effect of various concentration of electrolyte solution KMnO4 and K3[Fe(CN)6] on electricity produced by microbial fuel cell system with Lactobacillus bulgaricus in tofu whey substrate. The principle of this study was bioelectrochemistry that changes chemical energy into electrical energy which involves a redox reaction by utilizing microbes. This study used a microbe Lactobacillus bulgaricus and substrate tofu whey with 0.39 % carbohydrate content in dual chamber MFC system using a salt bridge as a conductor of protons from anode to cathode. Anode compartment contains a mixture of microbes that have been cultured and phosphate buffer with pH 7 while cathode compartment contained electrolytes KMnO4 or K3[Fe(CN)6] in some various concentration that is 0.25 M; 0.2 M; 0.15 M; 0.1 M and 0.01 M with added potassium phosphate buffer pH 7. The MFC system using Lactobacillus bulgaricus and substrate tofu whey with 0.39% carbohydrate content and electrolyte solution KMnO4 generated maximum potential difference of 99.2 mV at concentration of 0.2 M which was higher than system with electrolyte solution K3[Fe(CN)6] 0.2 M that produced maximum potential difference of 48.6 mV.